A Geographical Analysis of the Desertification Phenomenon and Its Impact on Date Production in Babylon Province - Hassan Yasser Al -Najim, Assist. Prof. Dr. Aqeel (Basra studies journal, 2026)
The problem of desertification is one of the most dangerous problems facing the development of agricultural activity in the era of the study, especially when it moves fixed sand dunes or form active sand dunes that immerse large areas of agricultural lands with sand, which turns them into desert areas that are not valid for agricultural investment, as the area of ​​the delicate lands in the study area reached to(1000) dunums. The sandy land has reached to (3710) dunums, while the lands threatened with desertification was(56992) dunums. The most important factors that exacerbate this phenomenon is the climate factor in the first place, as it is the basis for it to make the phenomenon and its diversity and production, as there are multiple varieties of dates such as Al -Maktoum - Al -Khudrawi - Al -Shukra - Al -Khasawi - Al -Hamrawi - Al -Zuhdi - Al -Barry - Al -Brain - Al –Sultani. This is one of the good items known as the governorate، but it witnessed a clear deterioration and was reflected in the decrease in the numbers of palm trees and their varieties due to a number of problems that classify the cultivation and production of dates، foremost of which are climate change، such as high temperatures، lack of rain، affecting the production and cultivation of palm trees in Babil Governorate، as well as government policies، wars، lack of material support for the farmer، lack of labor، spread of agricultural pests، and lack of demand for them The small number of manufacturers of dates products.